Case of anti‐NT5c1A antibody‐seropositive inclusion body myositis associated with severe dysphagia and prominent forearm weakness. Issue 1 (10th November 2022) - Matsui, Naoko; Takahara, Mika; Yamazaki, Hiroki; Takamatsu, Naoko; Osaki, Yusuke; Kaji, Ryuji; Nishino, Ichizo; Yamashita, Satoshi; Izumi, Yuishin
Abstract: We report a case of an 82‐year‐old woman with inclusion body myositis (IBM), who presented with severe dysphagia, finger flexor weakness, and respiratory dysfunction. In addition, the patient showed prominent forearm weakness with quadriceps sparing and was seropositive for the anti‐cytosolic 5′‐nucleotidase 1A (NT5c1A) antibody. The presence of the anti‐NT5c1A antibody is presumably associated with dysphagia. We speculate that the anti‐NT5c1A antibody is associated with the large discrepancy between distal upper limb weakness and proximal lower limb weakness in IBM.